International Journal of Clinical Dentistry and Research 2017
DOI: 10.5005/jp-journals-10060-0006
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Yen Angle and W Angle with ANB Angle, Wits Appraisal, and Beta Angle for Predicting Sagittal Jaw Dysplasia: A Cephalometric Study

Abstract: Introduction Sagittal jaw relationship is one of the basic criteria assessed for orthodontic diagnosis. ANB angle, Wits appraisal, and Beta angle are the most commonly used measures. Yen angle and W angle have been recently introduced. It was necessary to assess their predictability by comparing them with routinely used sagittal jaw indicators. Aim To assess Yen angle and W angle and compare them with ANB angle, Wits appraisal, and Beta angle in predicting sagittal jaw dysplasia. Materials and methods A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…In addition, Sundareswaran and Kumar's study evaluating the differences in the Beta angle between different malocclusion groups also reported that the Beta angle had higher values in HA cases, a finding that supports the results of our study (24). Similar to previous studies (9,21), it was determined that there are significant negative correlations between the ANB angle and Beta, W and Yen angles in both the total sample and each vertical face type. In a study conducted by Alhammadi et al, the Beta angle does not differ in individuals with Class I malocclusion and different vertical facial types (12).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, Sundareswaran and Kumar's study evaluating the differences in the Beta angle between different malocclusion groups also reported that the Beta angle had higher values in HA cases, a finding that supports the results of our study (24). Similar to previous studies (9,21), it was determined that there are significant negative correlations between the ANB angle and Beta, W and Yen angles in both the total sample and each vertical face type. In a study conducted by Alhammadi et al, the Beta angle does not differ in individuals with Class I malocclusion and different vertical facial types (12).…”
Section: Discussionsupporting
confidence: 91%
“…For this analysis, numerous cephalometric points, angular and linear measurements, and Badania kliniczne / Clinical research various analyses have been used (2)(3)(4)(5)(6)(7)14). Due to the large number of existing analytic methods, the same problem can be defined with different values (21). In our study, we aimed to evaluate the relationship between individuals with different vertical facial growth types in order to interpret the various parameters used in the definition of malocclusions in the sagittal dimension.…”
Section: Discussionmentioning
confidence: 99%
“…In our study the Skeletal Class I group shows that ANB Angle had significant moderate positive correlation with Pi Angle(r=0.411**). This result is in accordance with the study by Jain et al [16] and in contrast with the study by Kumar et al [12] while ANB Angle had significant moderate negative correlation with Beta Angle (r=-0.351**) which was supported by Bhardwaj et al, [17] Sharma et al, [18] Kapadia et al, [19] and ANB had non significant weak negative correlation with Yen Angle (r=-0.197) which is in accordance with the findings by Mittal et al, [14] Jain et al, [16] and W Angle (r=-0.199) Sharma et al, [18] Kapadia et al [19] . (Table -2)…”
Section: Discussionsupporting
confidence: 90%
“…In Skeletal Class I group it was found that Wits Appraisal had significant moderate negative correlation with Beta Angle(r=-0.351**) which is supported with study done by Bhardwaj et al, [17] Sharma et al, [18] Kapadia et al [19] and had significant moderate positive correlation with Pi Angle (r=0.338**) which is in accordance with results of Jain et al [16] and in contrast with the study conducted by Kumar et al [12] (Table -2) In Skeletal Class II group Wits had a significant strong negative correlation with Beta Angle. (r=-0.599**) which is in accordance with the study by Bhardwaj et al, [17] Sharma et al, [18] Kapadia et al [19] and non significant weak but positive correlation with Pi Angle (r=0.203) which favours the results of studies done by Jain et al [16] and Kumar et al [12] (Table -3) Beta Angle was introduced by Chong Yol Baik and Marie Ververidou. [10] They uses 3 Skeletal landmarks i.e Points A , Point B and apparent axis of condyle (Point C).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation